Von Hippel-Lindau Syndrome- A Case Report - Thulung, Suraj; Baniya, Ashish; Paudel, Subodh Sharma; Devkota, Anirudra; Shrestha, Shikher (Journal of Brain and Spine Foundation Nepal, 2020)
Von Hippel–Lindau (VHL) disease is a rare, familial disorder involving multiple organs, and characterized by the development of many benign and malignant tumors. It is an autosomal dominant disorder with high penetrance and variable expression. We present a case of a 31-year-old gentleman with gradual onset painless bilateral diminution in the vision for one and a half months with significant positive family history. Radiographic study revealed multiple cerebellar hemangioblastomas with obstructive hydrocephalus, renal cortical and pancreatic cysts and cystic renal cell carcinoma. Symptoms were relieved after endoscopic third ventriculostomy. These constellations of findings suggested von Hippel Lindau (VHL) syndrome and we present this case.